Concordance and Disconcordance of Serum Levels of Leptin with Leucocyte Telomere Length Across Spectrum of Adult Body Mass Index Among Indian Rural Population - Anurag Yadav; L G Nandakumar; Anmol Manaswini Golla Yadav; Srivats Golla Yadav; Kaveri N Karewad (Clinical and Research Journal in Internal Medicine, 2023)
Background: Obesity is a prominent avoidable cause of mortality and a growing health concern in both adults and children throughout the world. The study's goal is to measure leucocyte telomere length and its relationship with leptin throughout the BMI spectrum.